Analysis of Students' Mathematics Numeration Literacy In SPLDV Problems Viewed From Visual And Auditorial Learning Styles - Akhmad Nayazik (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Education has a vital role to face these challenges, education is a means of preventing risk, as well as a tool that can help improve the quality of human life in a sustainable manner. For this reason, current education is expected to be able to develop students to think creatively, be flexible, solve problems, collaborate and innovative skills needed for success in work and life. This study aims to explore the abilities and factors that influence students' numeracy literacy in solving problem problems in terms of visual and auditory learning styles in the material of the Two-Variable Linear Equation System. The type of research used in this research is qualitative research. Meanwhile, the method used is a case study. The case study method was chosen in order to be able to answer the research questions posed, namely to explore numerical literacy abilities and the factors that influence students' numeracy literacy in the SPLDV problem in terms of visual and auditory learning styles. Based on the results of the study, it can be concluded that students' mathematical numeracy literacy skills in SPLDV problem problems in terms of visual and auditory learning styles in class X TKR students and class X TB students at SMK Al Hikmah Bakalrejo, are still unsatisfactory where students in class X TKR only achieve an average an average of 60.7% of the practice questions worked on, while class X TB students only achieved an average of 38.9% of the practice questions worked on. This shows that the level of numeracy literacy is still low at the Al Hikmah Bakalrejo school. Keywords: mathematical numeracy literacy, SPLDV, visual and auditory learning styles.